A Hybrid Fuzzy Factor Analysis Model for Evaluation of Fiscal Proficiency - Poonam; Mangla, Monika; Sharma, Nonita; Yoosuf, Mohamed Sirajudeen (EAI Endorsed Transactions on Scalable Information Systems, 2023)
Fiscal Proficiency is one of the most significant priority for mankind as it has a key role in the escalation of the lifestyle. Hence, it plays an important role in the growth of individual, family and finally leads to the growth of the national economy. Here in this manuscript, authors present a fuzzy factor analysis model to determine and evaluate the factors that influence the fiscal proficiency. The application of fuzzy concepts to the statistical analysis deemed appropriate while investigating a nondeterministic report. Resultantly, authors present a Mamdani-based fuzzy model to evaluate the fiscal proficiency through various factors. The proposed model is proved to be an effective model and hence can be widely implemented in real life. Further, authors also recommend that the regulatory authorities should take efforts to promote fiscal proficiency that will lead towards escalation of national economy.